Platelet lysate as a serum replacement for skin cell culture on biomimetic PCL nanofibers. (19th May 2018) - Sovkova, Vera; Vocetkova, Karolina; Rampichova, Michala; Mickova, Andrea; Buzgo, Matej; Lukasova, Vera; Dankova, Jana; Filova, Eva; Necas, Alois; Amler, Evzen
Abstract: Platelets are a popular source of native growth factors for tissue engineering applications. The aim of the study was to verify the use of platelet lysate as a fetal bovine serum (FBS) replacement for skin cell culture. The cytokine content of the platelet lysate was characterized using the Bio-Plex system. The cells (fibroblasts, melanocytes, and keratinocytes) were cultured on PCL nanofibrous scaffolds to mimic their natural microenvironment. The cytokine content of the platelet lysate was determined, and to the cells, a medium containing platelet lysate or platelet lysate in combination with FBS was added. The results showed that 7% (v/v) platelet lysate was sufficient to supplement 10% (v/v) FBS in the culture of fibroblasts and keratinocytes. The combination of platelet lysate and FBS had a rather inhibitory effect on fibroblasts, in contrary to keratinocytes, where the effect was synergic. Platelet lysate did not sufficiently promote proliferation in melanocytes; however, the combination of FBS and platelet lysate yielded a better outcome and resulted in bipolar morphology of the cultured melanocytes. The data indicated that platelet lysate improved cell proliferation and metabolic activity and may be used as an additive to the cell culture media.